2022
DOI: 10.1371/journal.pone.0268318
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and analgesic effect of intrathecal fentanyl with bupivacaine in patients undergoing elective cesarean section; a prospective cohort study

Abstract: Background Spinal anesthesia with bupivacaine has side effects such as hypotension, respiratory depression, vomiting, and shivering. The side effects are dose-dependent, therefore different approaches have been attempted to avoid spinal-induced complications including lowering the dose of local anesthetic and mixing it with additives like Neuraxial opioids. Objective To compare the Hemodynamic and analgesic effects of intrathecal fentanyl as an adjuvant with low and conventional doses of bupivacaine in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
5
0
3
Order By: Relevance
“…In the group that received bupivacaine and fentanyl, there was a noticeable 36.6% incidence of complete motor block development, which was notably different from the group that only received bupivacaine. These findings are in line with previous research 9 . Interestingly, some authors have suggested that bupivacaine alone may be just as effective as the combination of bupivacaine and fentanyl in producing a quality motor block 17 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the group that received bupivacaine and fentanyl, there was a noticeable 36.6% incidence of complete motor block development, which was notably different from the group that only received bupivacaine. These findings are in line with previous research 9 . Interestingly, some authors have suggested that bupivacaine alone may be just as effective as the combination of bupivacaine and fentanyl in producing a quality motor block 17 .…”
Section: Discussionsupporting
confidence: 94%
“…Randomly allocated two distinct groups using sealed envelope technique were formed for the study. The sample size was calculated by using standard protocol and previous study 9 . Sample size (n)= ((Z_ (∝) +Z_β) ^ (2) ∝SD∝^2)/d^2 Where, SD (standard deviation = 2.52 as per previous study 9 ) and desirable error (d)=1, Confidence interval 95% CI =0.84, and the power of test at 80%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no statistical difference in the other side reactions, and all of which were mild and occured during administration, and usually return to normal before leaving the operation room. However, other studies suggested that esketamine did not increase maternal side effects [ 29 , 30 ], this discrepancy might due to the inconsistency with the observation time and administration mode. Therefore, the effect of a smaller dose of esketamine on postpartum depression should be studied in the future to reduce maternal discomfort.…”
Section: Discussionmentioning
confidence: 93%
“…However, post-spinal hypotension, relatively short duration,not sufficient postoperative analgesia are all the drawbacks of SA. A series of measures can compensate for the shortcomings of SA, such as neuraxial administration of opioids or a2 adrenergic receptor agonists, reducing the dosage of bupivacaine, can prolong the time for the first rescue analgesia, and reduce the occurrence of intraoperative hypotension [ 28 , 29 ]. Unfortunately, these measures are not routinely performed in our hospital, so no drugs other than local anesthetics were added into the subarachnoid space in this study.…”
Section: Discussionmentioning
confidence: 99%